Effect of Current Ratio, Debt To Equity Ratio and Debt To Asset Ratio on Return On Assets in Mining Companies in the Coal Sub-Sector : Companies Listed on the IDX in 2018-2021 - Rohmawati, Laila; Mursito, Bambang; Pawenang, Supawi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Lailia Rohmawati Effect of Current Ratio, Debt To Equity Ratio and Debt To Asset Ratio on Return On Assets in Mining Companies in the Coal Sub-Sector. Thesis Management Studies Program. Strata 1. Islamic University of Batik Surakarta. 2023. In the coal industry world with intense competition, it causes competition to develop and involves the importance of the organization's monetary exhibition. Concentrating on the organization's monetary performance is vital in terms of solvency, liquidity and solvency ratios. This study expects to decide the impact of CR, DER and DAR, on ROA in coal mining companies. It is hoped that it will provide knowledge about the impact of CR, DER, and DAR on ROA. This research is in the form of quantitative descriptive with secondary data types. the population of coal area mining organizations recorded on the IDX in 2018-2021 totaled 23 companies. Samples with purposive sampling amounted to 10 mining companies in the coal sector. The data collection method uses the annual financial report data documentation method. tested by multiple linear regression analysis. CR has signifficant negatif impact, DER has signifficant negatif impact, DAR has signifficant positif impact on ROA in Mining Companies in the Coal Sector. The consequences of the Assurance Coefficient Investigation got 83.5% where ROA can be made sense of by the free factors CR, DER, and DAR. Furthermore, can develop this research using other independent variables considering that there are still other independent variables such as Asset Turnover, EPS, TATO and other variables that can affect ROA.